Microbial community response to hydrocarbon exposure in iron oxide mats: an environmental study - Brooks, Chequita N.; Field, Erin K. (Frontiers in Microbiology, 2024)
Hydrocarbon pollution is a widespread issue in both groundwater and surface-water systems; however, research on remediation at the interface of these two systems is limited. This interface is the oxic-anoxic boundary, where hydrocarbon pollution from contaminated groundwaters flows into surface waters and where iron mats are formed by microaerophilic iron-oxidizing bacteria. Iron mats are highly chemically adsorptive and host a diverse community of microbes. To elucidate the effect of hydrocarbon exposure on iron mat geochemistry and microbial community structure and function, we sampled iron mats both up- and downstream from a leaking underground storage tank. Hydrocarbon exposed iron mats had significantly higher concentrations of oxidized iron and significantly lower dissolved organic carbon and total dissolved phosphate than unexposed iron mats. A strong negative correlation between dissolved phosphate and benzene was observed in the hydrocarbon exposed iron mats and water samples. There were positive correlations between iron and other hydrocarbons with benzene in the hydrocarbon exposed iron mats, unique from water samples. The hydrocarbon exposed iron mats represented two types, flocculent and seep, which had significantly different concentrations of iron, hydrocarbons, and phosphate, indicating that iron mat type is also important context in studies of freshwater mats. Using constrained ordination, we found the best predictors for community structure to be dissolved oxygen, pH, and benzene. Alpha diversity and evenness were significantly lower in hydrocarbon exposed iron mats than unexposed mats. Using 16S rDNA amplicon sequences, we found evidence of three putative nitrate-reducing iron-oxidizing taxa in microaerophile dominated iron mats (Azospira, Paracoccus, and Thermomonas). 16S rDNA amplicons also indicated the presence of taxa that are associated with hydrocarbon degradation. Benzene remediation-associated genes were found using metagenomic analysis both in exposed and unexposed iron mats. Furthermore, results indicated that season (summer vs. spring) exacerbates the negative effect of hydrocarbon exposure on community diversity and evenness and led to the increased abundance of numerous OTUs. This study represents the first of its kind to attempt to understand how contaminant exposure, specifically hydrocarbons, influences the geochemistry and microbial community of freshwater iron mats and further develops our understanding of hydrocarbon remediation at the land-water interface.